SCIENCE LEARNING AND CRITICAL THINKING ABILITIES OF JUNIOR HIGH SCHOOL STUDENTS - Sri Siswa Herawati; Suyidno Suyidno; Suryajaya Suryajaya; Fahmi Fahmi (Program Studi Pendidikan IPA, Universitas Lambung Mangkurat, 2024)
This research was conducted to produce learning tools that are suitable to support the improvement of students' critical thinking skills. More specifically, the tools developed are learning implementation plans, student worksheets, teaching materials, and learning outcome tests. The development model uses the Dick and Carey research model with research limitations on the validity and practicality aspects of learning tools. The results of the study show that in terms of validity, the tools developed have very valid results with achievements in the very good category as a result of the development carried out seriously in order to improve the quality of teaching and learning in the classroom.Keywords: Critical thinking, device development, science learning. Penelitian ini dilakukan menghasilkan perangkat pembelajaran yang layak untuk menunjang peningkatan kemampuan berpikir kritis peserta didik. Lebih spesifik perangkat yang dikembangkan adalah rencana pelaksanaan pembelajaran, lembar kerja peserta didik, materi ajar, dan tes hasil belajar. Model pengembangan menggunakan model penelitian Dick and Carey dengan batasan penelitian pada aspek kevalidan dan kepraktisan perangkat pembelajaran. Hasil penelitian menunjukan bahwa pada aspek validitas, perangkat yang dikembangkan memiliki hasil sangat valid dengan ketercapaian dalam kategori sangat baik sebagai akibat dari pengembangan yang dilakukan secara sungguh-sungguh demi memperbaiki kualitas belajar-mengajar di dalam kelas.Kata kunci: Berpikir kritis, pembelajaran IPA, pengembangan perangkat.